The Athena project : a thriller - Thor, Brad. (New York : Pocket Star Books, 2011)
A group of female warriors from the nation's most elite counter-terrorism unit-- the United States Army's 1st Special Forces Operational Detachment Delta--deploys on a dangerous international assignment. Their code name: Athena Project.
Keywords: United States. -- Army. -- Special Forces -- Fiction; Women intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; Spy stories; Suspense fiction